The temperature dependent lattice misfit of rhenium and ruthenium containing nickel-base superalloys – Experiment and modelling. (15th January 2021) - Neumeier, S.; Pyczak, F.; Göken, M.
Abstract: The lattice misfit between γ and γ' phase is a key parameter in Ni-base superalloys. Resulting internal coherency stresses govern the microstructure, its evolution and mechanical properties. Here, the influence of important alloying elements Re and Ru on the misfit up to 1100 °C is investigated. Due to their preferred partitioning to γ, the addition of both leads to a stronger increase of the lattice parameter of γ than of γ' and thus to a more negative misfit. The overall content of Re and Ru influences significantly the evolution of the misfit with temperature. Alloys with high contents show an atypical behavior, where the magnitude of the negative misfit gets smaller at high temperatures. Alloys with a medium content exhibit a rather constant misfit and alloys with a low content or without Re and Ru follow the typical trend of a more negative misfit with increasing temperature. The observed differences are ascribed to different thermal expansion coefficients and particularly to the changing chemical composition of γ due to the dissolution of γ' precipitates. An advanced model for determining the misfit based on thermodynamic calculations is presented. Different approaches for determining lattice parameters and calculating lattice misfits are evaluated in the supplementary. Graphical abstract: Unlabelled Image Highlights: Atypical behavior of 4 th generation Ni-base superalloys: the constrained lattice misfit reduces with increasing temperature The room temperature constrained lattice misfit gets more and more negative with increasing content of Re and Ru The course of lattice misfit depends mainly on the changing composition of γ due to the dissolution of γ' precipitates An advanced model for calculating and designing the temperature dependent constrained lattice misfit is presented [1 ]